Evaluation of efficiency of different radiotherapy methods for brain metastases in patients with lung cancer - Wolny, Edyta; Miszczyk, Leszek; Tukiendorf, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2005)
Lung cancer is the first most malignant cancer in men and 1/3 of cases are morbid and mortal. Lung cancer in women is second after breast cancer. Brain metastases occur in 40% to 60% of all cases. Median survival in the natural course of the cancer disease with brain metastases amounts to about 4 months. The application of treatment in the form of radiotherapy, surgery or radiosurgery causes prolongation of median survival from 3 to 5 months. The main treatment options for the management of brain metastases include whole-brain radiotherapy (WBRT), surgical resection +/- WBRT, radiosurgery (SRS), WBRT + SRS. In this retrospective work, we presented treatment options and we evaluated the influence of clinical factors on survival. We analyzed a group of 114 patients with lung cancer – 63 patients with non-small cell lung cancer (NSCL) and 51 patients with small-cell lung cancer (SCL). A solitary brain metastasis was detected in 50 patients. Two brain metastases were identified in 25 patients and three brain metastases were identified in 11. Multifocal brain metastases, of above 3 metastases, occurred in 28 patients. The treatment options, which were applied, in treatment of brain metastases were: WBRT – 68 patients, SRS – 33 patients and WBRT+SRS – 13 patients. In the present retrospective work, we evaluated the influence of clinical factors on patients’ survival. The factors are: high Zubrod performance, the number of metastases (fewer than 3) and the local control of the lung. Median survival of patients with lung cancer with brain metastases, is dependent on: the Zubrod performance, the number of metastases and local control of the main disease. Patients treated with the combination of WBRT and SRS have a chance of prolonging their survival.